A heterozygous variant in the SLC22A12 gene in a Sri Lanka family associated with mild renal hypouricemia - Vidanapathirana, Dinesha Maduri; Jayasena, Subashinie; Jasinge, Eresha; Stiburkova, Blanka (BMC pediatrics, 2018)
BACKGROUND: Renal hypouricemia is a rare heterogeneous inherited disorder characterized by impaired tubular uric acid transport, reabsorption insufficiency and /or acceleration of secretion. The affected individuals are predisposed to nephrolithiasis and recurrent episodes of exercise-induced acute kidney injury. Type 1 is caused by dysfunctional variants in the SLC22A12 gene (URAT1), while type 2 is caused by defects in the SLC2A9 gene (GLUT9). To date, more than 150 patients with the loss-of-function mutations for the SLC22A12 gene have been found (compound heterozygotes and/or homozygotes), most of whom are Japanese and Koreans. CASE PRESENTATION: Herein, we report a nine year old Sri Lankan boy with renal hypouricemia (serum uric acid 97 μmol/L, fractional excretion of uric acid 33%).The sequencing analysis of SLC22A12 revealed a potentially deleterious missense variant c.1400C > T (p.T467 M, rs200104135) in heterozygous state. This variant has been previously identified in homozygous and/or compound heterozygous state with other causative SLC22A12 variant c.1245_1253del (p.L415_G417del) in Roma population. CONCLUSIONS: This is the first identification of a family with mild renal hypouricemia1 associated to the p.T467 M variant. Detailed investigations of urate blood and urine concentrations in patients with unexplained hypouricemia are needed and renal hypouricemia should also be considered in patients other than those from Japan and/or Korea. Our finding confirms an uneven geographical and ethnic distribution of Romany prevalent SLC22A12 variant that need to be considered in Asian patients (population data Genome Aggregation Database: allele frequency in South Asia 0.007055, in East Asia 0.001330).
Keywords: URAT1; Renal Tubular Transport, Inborn Errors; Srí Lanka; Humans; Mutation, Missense; dítě; Child; Organic Cation Transport Proteins; Female; proteiny přenášející organické kationty; dospělí; Renal hypouricemia; Organic Anion Transporters; lidé; vrozené poruchy tubulárního transportu; Uric acid transporters; Sri Lanka; Urinary Calculi; močové kameny; předškolní dítě; Adult; missense mutace; ženské pohlaví; Male; přenašeče organických aniontů; Adolescent; Heterozygote; SLC22A12; heterozygot; mužské pohlaví; Child, Preschool; mladiství